An Analysis of Implicature in Stand-up Comedy : Mamat Alkatiri’s Jokes “Somasi” - Reja Ananda Sembiring; Charles David Marudut Silalahi; Justin Hubert Butar-Butar; Jonathan Marbun (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The goal of this study is to analyze of implicature in Stand-up Comedy : Mamat Alkatiri” Somasi” . To conduct this study, researchers used qualitative methodologies. Mamat Alkatiri’s Jokes, obtained from Youtube, served as the research's data source. This study relies on jokes by Mamat Alkatiri, that is implicature. This study used observation and implicature to collect the data. After we analyze, Mamat Alkatiri’s jokes were noted together with the implicature. The meaning research is then used to analyze the data. The examination of the lines from Mamat Alkatiri’s jokes that was done for the study of implicature. The situation described in the Mamat Alkatiri’s jokes serves as the implicature.